Effect Of Varying Dietary Lipid Levels In Snakehead Broodstock, Channa Striata On Egg, Larval Quality And Ontogenic Development Of Digestive Tract - Keong, Hui Lay (2017)
Snakehead or Channa striata, a freshwater fish well known for its nutraceutical values for wound healing is popular amongst the locals and also in Southeast Asia. Currently collection of seeds from the wild is declining due to over harvesting and environmental pollution. Artificial breeding is a feasible option practiced by commercial farms to meet to its high demand. However, traditionally trash fish is usually fed to snakehead broodstock which result in low quality seed production. Therefore good management of broodstock nutrition in captivity is significant.